Anti-sintering ZrO2-modified Ni/α-Al2O3 catalyst for CO methanation. Issue 25 (22nd February 2016) - Liu, Qing; Gu, Fangna; Zhong, Ziyi; Xu, Guangwen; Su, Fabing
Abstract : The ZrO2 -modified Ni/α-Al2 O3 catalysts prepared by a modified impregnation method show obvious enhancement of Ni anti-sintering because of the special distribution of ZrO2 nanoparticles on the surface of the catalyst. Abstract : To obviously reduce the sintering behavior of Ni particles in Ni/α-Al2 O3 catalysts during CO methanation reaction, ZrO2 was deposited onto the Ni/α-Al2 O3 catalyst surface by a modified impregnation method. It was observed that the ZrO2 -modified catalyst with an appropriate amount of ZrO2 showed enhanced catalytic activity due to the increased H2 uptake and Ni dispersion. During the 103h-lifetime test, the ZrO2 -modified catalyst exhibited higher stability and anti-sintering performance than the unmodified one, because the partial coverage of ZrO2 particles could effectively prevent Ni particles from sintering during the reaction at high temperatures. The findings obtained in this study should be conducive to the design and development of supported metal catalysts for high temperature reactions with enhanced stability.